Human factor-aware production scheduling in smart workshop - Pang, Alfred Chuan Hong (Nanyang Technological University, 2021)
A job shop will typically feature a set of machines that can be used in multiple different orders and combinations depending on the product or part that is produced. Humans are the ones who will be operating on the machines and completing the jobs and operations. Having a greater understanding of human factors and their impacts will greatly improve the allocation of resources optimally. Therefore, this project focuses on investigating the human factors in production scheduling. There will be optimisation of the input variables to produce minimum makespan desired. In this report, there will be further discussion and analysis of the results obtained to gain more insights of incorporating human factors in production scheduling.